Examining the physical education teacher concept related metaphor perceptions of secondary school students - Alpaslan Gorucu; Onur Koksal; Mustafa Uslu (Türk Spor ve Egzersiz Dergisi)
The purpose of the present research was to examine the perceptions of 6th Grade students (age range: 10-13 years old) regarding their concept of the physical education teacher expressed through metaphors and to analyze these metaphors for comparison between the genders. A total of 356 students (girls=184; boys=172) participated in the study during the 2014-2015 academic year. They were from three different state schools in the province of Konya, Turkey. According to the results, the students produced 67 different metaphors related to their concept of the physical education teacher. These metaphors were grouped under seven conceptional categories, namely “someone needed, guide, motivator; authoritarian, source of amusement, confidant and rude”. There were no statistically significant differences between the genders in terms of the metaphors used. The findings revealed that the metaphor method could be used meaningfully as an important data collection tool when investigating the perceptions of students regarding their concept of the physical education teacher. This method can be recommended for use in similar and further studies.